Systematic Review: Analisis Pengadaan Musik Kerja terhadap Produktivitas Kerja Tenaga Kerja - Alfayad, Afan; Dwiyanti, Endang (Preventia: The Indonesian Journal of Public Health, 2022)
This research was conducted to see the effectiveness of the procurement of work music on labor productivity. This study uses a systematic review method by finding 15 types of research articles, research articles are considered inclusion criteria based on PICOS (Population, Intervention, Comparison, Study Design Results, Year of Publication, and Language) as follows: 1) human sample, 2) work music intervention, 3) comparison of giving work music and not giving work music, 4) results: work productivity, 5) research articles, 6) articles published in 2012 until 2022, 7) in English and Indonesian. Procurement of work music is associated with increased worker productivity. This is indicated by research relevant to the increase in productivity. A 2014 study found that music had a significant effect on work morale and work productivity. This is also reinforced by evidence that the higher the morale, the higher the productivity of the workforce. Based on the results of a systematic review conducted, it shows that occupational safety and health programs in the form of procurement of work music are able to increase worker productivity found in various types of work so that they can optimally increase the benefits of the employer agency.